The Role of Notaries in Registration of Applications for Land Rights above Management Rights - Lukmanul Hakim; Taufan Fajar Riyanto; Andi Aina Ilmih (Sultan Agung Notary Law Review, 2022)
The purpose of this study was to analyze the role of a notary in registering applications for land rights over management rights. To analyze the process of determining land rights over management rights.The method used by the researcher isNormative JurisdictionandThe specifications in this study include descriptive analysis.The sources and types of data in this study are secondary data obtained from library studies. Based on the results of the study thatThe Role of Notaries in Application for Land Rights Above Management Rightsare: a. As a Consultant who provides legal counseling to clients; b. As an Authorized Person entrusted by his client for his competence and expertise.The process of determining land rights over management rights in the conception of legal certainty through procedures and complete requirements, namely a certificate of building use rights that is requested to be converted into a right of ownership, a deed of sale and purchase or a letter of acquisition regarding the land and the house in question, a letter of approval from the holder Mortgage Rights (if the land is encumbered with Mortgage Rights), Applicant's Identity Card, and Letter of Recommendation from Perum Perumnas. The granting or stipulation of land rights included in any settlement of land issues is intended as an effort to provide legal certainty guarantees for the holders of the rights.